Marriage disputes in medieval England - Pedersen, Frederik (Online Access with DDA: GOBI Pick and Choose., 2000)
Most information about medieval life comes from the records of the church courts of the province of York, which date from the 14th century. This work investigates cases involving a range of disputes, including sex, consent and violence.